Synthesis, physicochemical, thermal, fluorescence and catalytic activity studies of novel Mn(II), Co(II), Ni(II) and Cu(II) complexes with tridentate (ONS) Schiff base ligand - Ayoub, Manara Ahmed; Abd-Elnasser, Eman Hamed; Ahmed, Mona Abdel-Aziz; Rizk, Marium Girgis (European Journal of Chemistry, 2017)
Syntheses and physicochemical studies of Mn(II), Co(II), Ni(II) and Cu(II) complexes with tridentate Schiff base ligand (E)-2-((1-(thiophen-2-yl)ethylidene)amino)phenol (HL)(ATS) were characterized by elemental analysis, FT-IR, Mass, 1H NMR, UV-Vis, magnetic moment, thermal analysis (TG and DTG) techniques, molar conductance and fluorescence spectra. The IR spectra showed that complexes were coordinated in metal ions via the imine N, O and S atoms. Magnetic and UV-Vis spectra, indicated that the geometrical structure of Mn(II), Co(II) and Ni(II) complexes are an octahedral while Cu(II) is a tetrahedral. The kinetic thermodynamic parameters such as E*, DH*, DS* and DG* were determined for each thermal degradation stage of TG curves of the metal(II) complexes using Coat-Redfern method. Fluorescence studies indicated that the Schiff base ligand HL(ATS), and its metal(II) complexes can serve as potential photoactive materials as indicated from their characteristic fluorescence properties and study the effect of solvent and pH on it. The catalytic activities of metal(II) complexes were studied using H2O2 solution.